Comparing the use of rhetorical appeals by two Malaysian politicians in their social media communication / Nor Ashikin Ab Manan and Alia Izzati Sham Shul Shukri - Ab Manan, Nor Ashikin; Sham Shul Shukri, Alia Izzati (Universiti Teknologi MARA, Sabah, 2023)
Drawing upon Aristotle’s rhetorical appeal theory, the study was conducted to compare the use of rhetorical strategies by two Malaysian politicians namely Syed Saddiq [P1] and Hannah Yeoh [P2] in their social media communication. Two research questions were formulated for the study: (a) What were the rhetorical strategies used by the two politicians? (b) Which type of rhetorical appeals were used the most among the two politicians? This study employs a qualitative content analysis approach and the data for the study were social media postings collected from the target politicians’ social media platforms (Facebook and Twitter) related to the Taman Sri Muda flood crisis dated from the 17th of December 2021 to the 10th of January 2022. The data were analysed and classified based on Aristotle’s rhetorical appeals of ethos, pathos, and logos. It was found that both politicians adopted different types of rhetorical strategies depending on the message they intended to convey. Syed Saddiq [P1] used more pathos while Hannah Yeoh [P2] utilised more ethos. It can be concluded based on the findings that Syed Saddiq and Hannah Yeoh had utilised Aristotle’s rhetorical appeals of ethos, pathos, and logos in their social media posts during the Taman Sri Muda flood crisis to establish their credibility as politicians, to appeal to the public’s emotion and sympathy as well as to provide evidence to back up their arguments and claims. This study contributes to the literature on persuasive strategies used by politicians and political communication.